Applying Community of Inquiry for Language Learning Among English Preservice Teachers - Rully Agung Yudhiantara (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
Community of Inquiry allows learning activities to run optimally. There are three components in CoI: teaching presence, social presence and cognitive presence. This study aims to investigate the implementation of CoI among English Language Education students in lectures, their opinions, the components of teaching presence, cognitive presence and social presence that arise. The method used in this research is qualitative. Data were collected through observation, Focus Group Discussion and Content Analysis. The results of the study show that CoI can be implemented for lecture activities among English Education students. They argue that CoI provides many benefits for their lecture activities. The components of teaching presence, social presence and cognitive presence appear in learning activities during the implementation of CoI.